Busts of Dr BR Ambedkar, Chhatrapati Shivaji Maharaj and Veer Savarkar - Ghosh, Ayan (Jio Institute, 2023)
The Corporation Hall has a collection of busts and statues of prominent personalities from Indian history, freedom fighters and eminent citizens of Mumbai who contributed greatly in the development of the city. Seen here are the busts of Dr B.R. Ambedkar, Chhatrapati Shivaji Maharaj and Vinayak Damodar Savarkar.